Morphosedimentary and hydrographic features of the northern Argentine margin: The interplay between erosive, depositional and gravitational processes and its conceptual implications - Preu, Benedict; Hernández Molina, F. Javier; Violante, Roberto Antonio; Piola, Alberto Ricardo; Paterlini, C. Marcelo; Schwenk, Tilmann; Voigt, Inés; Krastel, Sebastian; Spiess, Volkhard (Deep Sea Research Part I: Oceanographic Research Papers)
Bottom currents and their margin-shaping character became a central aspect in the research field of sediment dynamics and paleoceanography during the last decades due to their potential to form large contourite depositional systems (CDS), consisting of both erosive and depositional features. A major CDS at the northern Argentine continental margin was studied off the Rio de la Plata River by means of seismo- and hydro-acoustic methods including conventional and high-resolution seismic, parametric echosounder and single and swath bathymetry. Additionally, hydrographic data were considered allowing jointly interpretation of morphosedimentary features and the oceanographic framework, which is dominated by the presence of the dynamic and highly variable Brazil–Malvinas Confluence. We focus on three regional contouritic terraces identified on the slope in the vicinity of the Mar del Plata Canyon. The shallowest one, the La Plata Terrace (∼500 m), is located at the Brazil Current/Antarctic Intermediate Water interface characterized by its deep and distinct thermocline. In ∼1200 m water depth the Ewing Terrace correlates with the Antarctic Intermediate Water/Upper Circumpolar Deep Water interface. At the foot of the slope in ∼3500 m the Necochea Terrace marks the transition between Lower Circumpolar Deep Water and Antarctic Bottom Water during glacial times. Based on these correlations, a comprehensive conceptual model is proposed, in which the onset and evolution of contourite terraces is controlled by short- and long-term variations of water mass interfaces. We suggest that the terrace genesis is strongly connected to the turbulent current pattern typical for water mass interfaces. Furthermore, the erosive processes necessary for terrace formation are probably enhanced due to internal waves, which are generated along strong density gradients typical for water mass interfaces. The terraces widen through time due to locally focused, partly helical currents along the steep landward slopes and more tabular conditions ...